Part A: The stability of Adenoviral and mRNA based COVID-19 vaccines and the potential of HSA/ Part B: Characterisation of IgG A33 hFab’ and human serum albumin using hydrodynamic methods - Abu Hammad, Khalil (2021)
Part A: At the end of 2019, the SARS-COV-2 virus was observed to cause respiratory disease, and it is responsible for the high number of patients admitted to hospital. Many biopharmaceutical / biotechnology companies have started manufacturing vaccines that can prevent the SARS-COV-2 virus. An important issue is COVID-19 vaccine stability, one of the most frequently stated problems faced through vaccination programs particularly in the high temperatures low-income countries. Along with cost, availability, and delivery – stability makes delivery simple. This review analyses the characteristics of the two common groups of COVID-19 vaccines – Adenovirus based (such as the Oxford/AstraZeneca and Janssen vaccines) and mRNA based (such as Pfizer/BioNTech and Moderna) – and in particular the potential application of human serum albumin (HSA) as a stabiliser for the mRNA COVID-19 platform. From the stability point of view, while the Adenoviral vector-based vaccines can be stabilised and stored at 2–8 °C range yielding 6 months shelf-life, the mRNA-based vaccines have to be stored at much lower temperatures, limiting their distribution to the higher temperature regions. This emphasise the importance of research into formulation solutions, such as the use of excipients like human serum albumin, to improve these products stability and, therefore facilitate vaccination programs without the need for cold chain storage. The availability of these vaccines to lowincome countries would have a major role in lowering the cases of COVID-19 infections. In future investigations, it is possible to look at different unstable COVID-19 platforms by applying new technologies for making a stabilise vaccine.